2022
DOI: 10.1063/5.0083711
|View full text |Cite
|
Sign up to set email alerts
|

Study of surface tension effects on near-wall cavitation bubble collapse with a pseudopotential lattice Boltzmann model

Abstract: A lattice Boltzmann pseudopotential cavitation model with tunable surface tension and large density and viscosity coefficient ratios was used to simulate near-wall cavitation bubble collapse. The influences of the surface tension, bubble–wall distance, and initial pressure difference on the flow field distribution were analyzed, and the relationships between the surface tension and maximum micro-jet and collapse pressure were investigated. The results indicated that a lower surface tension intensifies the defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The influence of individual parameters in controlled laboratory studies is presented in many scientific papers. The influence of surface tension on the cavitation bubble dynamics was also evaluated in [101]. The results of this study showed that lower surface tension increases the deformation of the gas-liquid interface, which leads to a more concentrated microstructure.…”
Section: Recommendations For Finding New Expressions Of the Cavitatio...mentioning
confidence: 94%
“…The influence of individual parameters in controlled laboratory studies is presented in many scientific papers. The influence of surface tension on the cavitation bubble dynamics was also evaluated in [101]. The results of this study showed that lower surface tension increases the deformation of the gas-liquid interface, which leads to a more concentrated microstructure.…”
Section: Recommendations For Finding New Expressions Of the Cavitatio...mentioning
confidence: 94%